The Influence of Leadership Style and Work Environment on the Performance of Perum Perhutani KPH Surakarta Employees - Afiddatul Jannah; Suhartini Suhartini; Alldila Nadhira Ayu Setyaning (Journal of Education Technology Information Social Sciences and Health, 2024)
One of the factors that determines the success of an organization is the performance of human resources. Leadership style is the way a leader behaves, communicates and interacts with other people in influencing other people to do something. The work environment is the main part that is able to improve the quality of work productivity, where the work environment is the social, physical and psychological life in an organization. This research aims to determine the influence of leadership style and work environment on employee performance at Perum Perhutani KPH Surakarta. The data used is in the form of a questionnaire that has been distributed to all employees of Perum Perhutani KPH Surakarta. Data analysis was carried out using SPSS software where the results indicated that leadership style had a positive but not significant influence on employee performance and the work environment did not have a positive or significant influence on employee performance.